Financial regulation in the EU: Cross-border capital flows, systemic risk and the European Banking Union as reference points for EU financial market integration - Brigitte Haar (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
This is a chapter for a forthcoming volume Oxford Handbook of Financial Regulation (Oxford University Press 2014) (eds. Eilís Ferran, Niamh Moloney, and Jennifer Payne). It provides an overview of EU financial regulation from the first banking directive up until its most recent developments in the aftermath of the financial crisis, focusing on the multiple layers of multi-level governance and their characteristic conceptual difficulties. Therefore the paper discusses the need to accommodate cross-border capital flows following from the EU internal market and the resulting regulatory strategies. This includes a brief overview of the principle of home country control and the ensuing Financial Services Action Plan. Dealing with the accommodation of cross-border capital flows and their regulation necessarily require an orchestration of the underlying supervisory structures, which is therefore also discussed. In the aftermath of the financial crisis of 2007-09 an additional aspect of necessary orchestration has emerged, that is the need to control systemic risk. Specific attention is paid to microprudential supervision by the newly established European Supervisory Authorities and macroprudential supervision in the European Banking Union, the latter's underlying drivers and the accompanying Single Supervisory Mechanism, including the SSM's institutional framework as well as the consideration of its rationales and the Single Resolution Mechanism closely linked to it.
urn:nbn:de:hebis:30:3-344445
Keywords: G21; G28; G38; K22; K23; 330; Financial regulation; systemic risk; microprudential supervision; European Banking Authority; macroprudential supervision; European Systemic Risk Board; European Banking Union; Single Supervisory Mechanism